2017
DOI: 10.1075/btl.129.14cli
|View full text |Cite
|
Sign up to set email alerts
|

Child language brokers’ representations of parent–child relationships

Abstract: The Open University's repository of research publications and other research outputs Child language brokers' representations of parent-child relationships Book Section How to cite:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Views about the impact of child language brokering on the dynamics of family relationships demonstrate a mixed picture. Some studies suggest a stronger bond between parents and children (Chao, 2006; Orellana, 2009) especially when accompanied with a strong sense of family togetherness and community connection, alongside praise or appreciation for their activities (Cline et al, 2017; Tomasi & Narchal, 2020). Other scholars have documented associations with negative feelings such as stress, burden and depression, especially when associated with poor parenting relationships (Kim et al, 2017; Tomasi & Narchal, 2020; Wu & Kim, 2009).…”
Section: Child Language Brokering As a Family Practicementioning
confidence: 99%
“…Views about the impact of child language brokering on the dynamics of family relationships demonstrate a mixed picture. Some studies suggest a stronger bond between parents and children (Chao, 2006; Orellana, 2009) especially when accompanied with a strong sense of family togetherness and community connection, alongside praise or appreciation for their activities (Cline et al, 2017; Tomasi & Narchal, 2020). Other scholars have documented associations with negative feelings such as stress, burden and depression, especially when associated with poor parenting relationships (Kim et al, 2017; Tomasi & Narchal, 2020; Wu & Kim, 2009).…”
Section: Child Language Brokering As a Family Practicementioning
confidence: 99%
“…This research has also revealed how language brokers in these conferences are subject to multiple forms of surveillance (Reynolds et al, 2015). Using vignette methodology, researchers have inquired individual stances of youth on language brokering and competing demands of autonomy and connectedness in the relationship between children and parents (Cline et al, 2017). With narrative methods, researchers have inquired how adults who have grown up brokering for their parents construct their childhood language brokering experiences and how adults’ views of their own language brokering practices as children change over time (Bauer, 2013; Orellana and Phoenix, 2017).…”
Section: Language Brokering and Language Education Policies In Schoolsmentioning
confidence: 99%
“…There has been a long-standing debate within research on child language brokering, balanced with understandable discomfort, about the kind of advocacy or intermediary role that children and young people might play on behalf of their family (Cline et al, 2017; Orellana, 2009; Valdés, 2003). In her study with adults reflecting on their child language brokering experiences, Bauer (2017) describes brokers’ abilities to edit or censor information as a capacity for active agency, which may be enabled or constrained by the social context (Callaghan et al, 2018).…”
Section: Positioning the Self As An Active Brokermentioning
confidence: 99%